La tragicomedia de la administración municipal en La Ley de Herodes (Tema Central) - Chávez Huanca, Eddy (2019)
This article relates through an analysis of the movie The Law of Herod, the exercise of local power, municipal precariousness and corruption in which the municipal authorities are not infrequently involved. We see the degradation of Juan Vargas, the Mayor of the town, as he uses the law to give an apparent legality to his illicit acts in order to sustain himself in power and subdue the population. Thus, cinema is an ideal instrument for discussing difficult issues such as corruption and its connotations that end up establishing a culture of illegality that challenges the ethics and effectiveness of law.